Comparative efficacy of herbal essences with amphotricin B and ketoconazole on Candida albicans in the in vitro condition - Shahin Gavanji; Sayed R. Zaker; Zahra G. Nejad; Azizollah Bakhtari; Elham S. Bidabadi; Behrouz Larki (Integrative Medicine Research)
Background: The Candida species are the most important factors of fungal infections in humans and animals. It is necessary to prepare antifungal or antimicrobial drugs because of increasing drug resistance. The natural treatment of diseases of bacterial origin using medicinal plants is important. In this study the effect of antimicrobial medicinal herbal essential oils and conventional antifungal drugs were evaluated on Candida albicans in vitro. Methods: Disc diffusion assay and the microbroth dilution method were used to investigate the anticandidal effects of Foeniculum vulgare Mill, Satureja hortensis L, Cuminum cyminum, and Zataria multiflora Boiss essential oils. The anticandidal effect of these essential oils was compared with that of amphotricin B and ketoconazole in vitro. We then measured the chemical composition of the studied essential oils using gas chromatography–mass spectroscopy. Results: Z. multiflora Boiss essential oil at the minimum inhibitory concentration (MIC) of 34 μg/mL and minimal lethal concentration [i.e., minimal fungicidal concentration (MFC)] of 64 μg/mL had more powerful anti-Candida activity than the other essential oils. C. cyminum essential oil showed the least effect on the tested fungus. A comparison of the effect of the studied essential oils and antifungal drugs showed that the antifungal effect on the C. albicans fungus was better with the fungicides than with the essential oils. Conclusion: In the present study, essential oils with different components showed antifungal activity (especially Z. multiflora Boiss essential oil). They can therefore be used as new antifungal substances.